BMP: Ribbon Barriers - Kati W. Migliaccio; Brian Boman; Jemy Hinton; Kevin Hancock (EDIS)
ABE-383, a 2-page illustrated fact sheet by Kati W. Migliaccio, Brian Boman, Jemy Hinton, and Kevin Hancock, addresses a specific set of Best Management Practices that can be described as ribbon barriers. Includes references. Published by the UF Department of Agricultural and Biological Engineering, October 2008.